IN VITRO POTENCY AND TOXICITY OF STREPTOMYCES SP. FERMENTATION PRODUCT AS AN ANTIMALARIAL THERAPY AGAINST PLASMODIUM FALCIPARUM - SETYANINGSIH, YUNI; LATIF, ABDUL; ASTUTY, HENDRI; SYAFRUDDIN, DIN; ASIH, PUJI BUDI SETIA (International Journal of Applied Pharmaceutics, 2019)
Objective: This research aims to study the activity of a Streptomyces sp. fermentation product as an antimalarial modality in HepG2 cells. Methods: The effects of the product against Plasmodium falciparum 3D7 were examined using an in vitro technique parasite. The potency of the Streptomyces sp. fermentation product was examined by determining the half maximal inhibitory concentration (IC50), and the mechanism was studied using transmission electron microscopy (TEM). Toxicity tests were also conducted. Results: The Streptomyces sp. fermentation product had an IC50 of 0.001 μg/ml against the parasite, versus values of 0.054 and 0.022 μg/ml for quinidine and prodigiosin, respectively. TEM revealed no formation of hemozoin. The Streptomyces sp. fermentation product was non-toxic in HepG2 cells based on its cytotoxicity concentration 50% of 1.380 μg/ml. Conclusion: The Streptomyces sp. fermentation product has potential as a potent and non-toxic antimalarial therapy.